Antioxidative, antimicrobial and anti-inflammatory activities and release of ultra-filtered antioxidative and antimicrobial peptides during fermentation of sheep milk: In-vitro, in-silico and molecular interaction studies. (June 2022) - Ashokbhai, Jodhani Keyur; Basaiawmoit, Bethsheba; Das, Sujit; Sakure, Amar; Maurya, Ruchika; Bishnoi, Mahendra; Kondepudi, Kanthi Kiran; Padhi, Srichandan; Rai, Amit Kumar; Liu, Zhenbin; Hatia, Subrota
Abstract: The antioxidative, antimicrobial, and anti-inflammatory properties of fermented sheep milk with L. fermentum (KGL4), as well as the generation of antioxidative and antimicrobial peptides, are evaluated in the study. Antioxidative and antibacterial activities in sheep milk fermented with KGL4 increased with incubation hours, along with varied antioxidative properties (ABTS assay: 35.12%, hydroxyl free radical scavenging assay: 29.12%, superoxide free radical scavenging activity: 36.38%). Antimicrobial activity of fermented sheep milk against E. faecalis (19 mm), S. typhimurium (15.67 mm), B. cereus (14 mm), and E. coli (13 mm) was also observed. Furthermore, after 48 h, the KGL4 showed maximum proteolysis (10.40 mg/ml) at 2.5% rate of addition sheep milk. The antioxidative and antimicrobial activities of fermented sheep milk fractions (3 kDa and 10 kDa permeates and retentates) were also investigated. The highest ABTS activity (26.90%) was found in 10 kDa permeate, whereas the 3 kDa retentate had higher hydroxyl free radical scavenging activity (69.20%) and 3 kDa permeate showed maximum superoxide free radical scavenging activity (32.85%). The 10 kDa retentate had shown maximum antimicrobial activity against S. typhimurium (13.67 mm) and E. faecalis (17.00 mm). Proteins spotted on 2D gel electrophoresis of KGL4 were varied from 10 to 70 kDa. RP-LC/MS was used to identify 5 novel peptide sequences from 2-D gel spots. Searches in the BIOPEP database confirmed the antioxidative and antimicrobial effects of the novel fermented sheep milk peptides. Fermented sheep milk with KGL4 (SMKGL4) significantly reduced excessive TNF-α, IL-6, & IL-1β production in LPS-activated RAW 264.7 cells. Graphical abstract: Image 1 Highlights: The study aims to evaluate novel antioxidative and antibacterial peptides in sheep milk fermented with Lactobacillus fermentum KGL4. Fermented sheep milk significantly reduced excessive TNF-α, IL-6, & IL-1β production in LPS-activated RAW 264.7 cells. RP-LC/MS was used to identify 5 peptides from 2D gel electrophoresis followed by SDS-PAGE on BIOPEP databases. The peptide FAWPQYLK showing significant binding affinity and interactions at the binding sites of Ef- HMGCS and Ef-DHFR.